If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4(x + -6) = 3(x + 2) Reorder the terms: 2x + 4(-6 + x) = 3(x + 2) 2x + (-6 * 4 + x * 4) = 3(x + 2) 2x + (-24 + 4x) = 3(x + 2) Reorder the terms: -24 + 2x + 4x = 3(x + 2) Combine like terms: 2x + 4x = 6x -24 + 6x = 3(x + 2) Reorder the terms: -24 + 6x = 3(2 + x) -24 + 6x = (2 * 3 + x * 3) -24 + 6x = (6 + 3x) Solving -24 + 6x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -24 + 6x + -3x = 6 + 3x + -3x Combine like terms: 6x + -3x = 3x -24 + 3x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 -24 + 3x = 6 + 0 -24 + 3x = 6 Add '24' to each side of the equation. -24 + 24 + 3x = 6 + 24 Combine like terms: -24 + 24 = 0 0 + 3x = 6 + 24 3x = 6 + 24 Combine like terms: 6 + 24 = 30 3x = 30 Divide each side by '3'. x = 10 Simplifying x = 10
| -3(2y+5)+4(3y-6)= | | -8+7+4x=69 | | 7m-25=2n | | 3x^6-24x^3=0 | | 7x-42=2x+38 | | 2z-7z=-z-1-9z | | 4x+9+x=-6 | | 8m-4=8m | | -15x-15=90 | | X-2.16=9.87 | | 12x-12=4+6x | | 3/x=9/25 | | X-9.7=7.8 | | 29,000,000/X=8.57 | | 9z+6z=7z-6+3z | | -3(4t+5)+7(3t-4)= | | -6(3x-4)=120 | | t−8=5(t/3−8 | | 86=x+6x+9 | | 18x+6=2x-9x | | 9x/5-33=3 | | 73=4x+5x+10 | | 6a+18=0 | | x+124=431 | | 0.2(d-2)=0.3d+5-3+0.1d | | 3(x+4)+4(7x-3)= | | 6x+2=2x-7x | | 9p=6p+22 | | (6-2x)+2=10 | | 4y+3=31 | | t−8=5(t/3−8) | | 3x-54=6 |